INCREASING STUDENTS’ LISTENING SKILLS USING SPOTIFY AT SMK LANIANG MAKASSAR - Arung, Stevany Datu; Muhayyang, Maemuna; Aeni, Nur (JTechLP: Journal of Technology in Language Pedagogy, 2025)
The purpose of this research is to determine whether the use of the Spotify application can improve students' listening skills. This research used a quantitative approach with a purposive sampling technique and used a pre-experimental design. The population of this research consisted of XI Nursing class students of SMKS Laniang Makassar, South Sulawesi, with a sample size of 27 students. Data collection was done through pre-test and post-test. The results of the analysis showed that the mean value of the pre-test was 59.22 with a classification of “very poor” and the mean value of the post-test was 74.11 with a classification of “good”, the probability value (sig. 2-tailed) < 0.001, which is lower than the significance level of 0.05. The researcher found that the H0 was rejected and H1 was accepted. Based on the results of data analysis, the researcher concluded that the use of the Spotify application improves students' listening skills at SMK Laniang Makassar.